2009
DOI: 10.1051/forest/2009003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of some ecological variables on carabid communities in native and non native forests in the Ibaizabal basin (Basque Country: Spain)

Abstract: Abstract• Carabid beetles were investigated at five different forest types in the Ibaizabal basin (northern Spain). The landscape is characterized by the presence of remnants of native forest surrounded by conifer plantations.• Carabids were trapped in 52 stands of mixed forest, beech forest, holm oak forest, mixed pine and Monterey pine plantations in 2005 and 2006. The main objectives of the study were: compare carabid diversity, recognise the characteristic species, and study the effects of ecological varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…There are studies showing a reduced carabid species richness in plantations compared to forests (da Silva et al 2008;Fahy and Gormally 1998;Magura et al 2003) or a lower number of forest specialist species (Fuller et al 2008). On the other hand, it was shown that carabid beetle assemblages of mature plantations do not significantly differ from those of natural or semi-natural forest (Elek et al 2010;Karen et al 2008;Martinez et al 2009), indicating that the establishment of tree plantations will not Fig. 4 NMS ordination of carabid communities at the 13 sample sites: (filled triangle) rubber plantation; (empty square) grassland and shrubland; (empty square) rice field fallow; (filled circle) forest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are studies showing a reduced carabid species richness in plantations compared to forests (da Silva et al 2008;Fahy and Gormally 1998;Magura et al 2003) or a lower number of forest specialist species (Fuller et al 2008). On the other hand, it was shown that carabid beetle assemblages of mature plantations do not significantly differ from those of natural or semi-natural forest (Elek et al 2010;Karen et al 2008;Martinez et al 2009), indicating that the establishment of tree plantations will not Fig. 4 NMS ordination of carabid communities at the 13 sample sites: (filled triangle) rubber plantation; (empty square) grassland and shrubland; (empty square) rice field fallow; (filled circle) forest.…”
Section: Discussionmentioning
confidence: 99%
“…The poor habitat quality of patchy native forest remnants enclosed by plantations was assumed to be the main factor explaining the high similarity in carabid diversity of the two habitat types in the study of Martinez et al (2009).…”
Section: Discussionmentioning
confidence: 99%
“…We characterized each plot in terms of variables related to the litter layer, which serves as the beetle's habitat, in terms of variables that can be related to the land use history of the plot, in terms of variables that can be related to local population size, and also in terms of variables related to soil, vegetation, climate, geography, and forest management. To characterize our plots in terms of general parameters known to affect ground beetles and therefore Abax parallelepipedus (for general overview see [ 67 ], with specific references listed for each variable), we used longitude [ 68 ], latitude [ 69 ], elevation [ 70 , 71 ], mean annual temperature [ 71 , 72 ], mean annual precipitation [ 71 ], forest management type [ 53 ], main tree species [ 53 ], number of vascular plant species [ 51 , 73 ], soil type [ 74 ], soil pH [ 75 ], and the Forest Management Intensity index (FORMI) ([ 53 ], defined in [ 76 ]). Depth of the litter layer and ground cover of litter, of deadwood, and of trees (see [ 77 , 78 ]) were included to characterize the habitat of the beetle and thus local population sizes.…”
Section: Methodsmentioning
confidence: 99%
“…'' In ecological impact studies carabid beetles are frequently cited as indicators in the vague sense, but according to Landres et al (1988) strict definition they should more often be cited as model or study organisms. Many studies have tested the effects of environmental variables on carabids: amongst other things they have been used to measure effects of forest fragmentation (Fujita et al 2008;Gaublomme et al 2008), forest management (Koivula 2002;Fuller et al 2008;Martinez et al 2009;Maleque et al 2009), climate change (Scott and Anderson 2003;Eyre et al 2005), agricultural practices (Desender and Bosmans 1998;Irmler 2003), land cover variables (Eyre et al 2003;Small et al 2006), biodiversity (Pizzolotto 1994;Duelli and Obrist 1998), pollution (Heliövaara and Väisänen 1993;Avgn and Luff 2010), salt stress (Petillon et al 2008), insecticides (Everts et al 1985;Walsh et al 1993;Frampton and Ç ilgi 1994), environmental classification (Casale 1990;Dufrêne et al 1990;Eyre and Luff 1990;Mossakowski et al 1990;Zulka 1994), urbanization (Magura et al 2010), habitat quality (Heijerman and Turin 1994) and management of urban roundabouts (Jones 2010). Studies such as these test for effects on carabid populations and often lead to habitat management conclusions without testing for the effects of management strategies on other groups of organisms.…”
Section: Introductionmentioning
confidence: 99%